Nurses’ training evaluation: An assessment of effective transfer of simulation training - Sharma, Poonam; Sharma, Pooja; Herbert, Jaideep; K. Singh, Manish (International Journal of Nursing Research, 2023)
Objective: The question that laid the foundation for this study was whether simulation-based training for new nurses, hired in a multispecialty hospital in Delhi, NCR Region, is effective in terms of implementation of learnings as effective clinical practice in in-patient wards. The study relied on Kirkpatrick’s model of effectiveness to assess the impact of the technical training imparted to the nurses. The objective of the study was to assist HR departments, in hospitals, to make evidence-based decisions, on such future initiatives, for improved clinical performance by nurses. Method: A sample size of 178 newly recruited nurses was studied over a period of five months. These nurses underwent a mandatory 40 hours simulation training program conducted by credentialed trainers. The descriptive study evaluated the impact of training, at the prescribed Level 1, 2 and 3 of Kirkpatrick’s model of effectiveness, by investigating the degree of change in clinical skills, measured by a self-rated tool before and after training, designed by the trainers. Results: An analysis of the pre and post-training test demonstrated a significant improvement in the learning levels of the new nurses and an association between learning and transforming of learning into practice has been identified. Conclusion: The study shows a positive learning outcome and transfer of skills in the real work area hence confirming a positive association between the first three levels of Kirkpatrick’s model. We, therefore, recommend that HR departments of hospitals should encourage simulation training initiatives to be able to improve their nurses’ performance and keep them updated on latest clinical techniques.